Eight questions about physician-rating websites: a systematic review. - Emmert, Martin; Sander, Uwe; Pisch, Frank (Journal of Medical Internet Research, 2013)
BACKGROUND Physician-rating websites (PRWs) are currently gaining in popularity because they increase transparency in the health care system. However, research on the characteristics and content of these portals remains limited. OBJECTIVE To identify and synthesize published evidence in peer-reviewed journals regarding frequently discussed issues about PRWs. METHODS Peer-reviewed English and German language literature was searched in seven databases (Medline (via PubMed), the Cochrane Library, Business Source Complete, ABI/Inform Complete, PsycInfo, Scopus, and ISI web of knowledge) without any time constraints. Additionally, reference lists of included studies were screened to assure completeness. The following eight previously defined questions were addressed: 1) What percentage of physicians has been rated? 2) What is the average number of ratings on PRWs? 3) Are there any differences among rated physicians related to socioeconomic status? 4) Are ratings more likely to be positive or negative? 5) What significance do patient narratives have? 6) How should physicians deal with PRWs? 7) What major shortcomings do PRWs have? 8) What recommendations can be made for further improvement of PRWs? RESULTS Twenty-four articles published in peer-reviewed journals met our inclusion criteria. Most studies were published by US (n=13) and German (n=8) researchers; however, the focus differed considerably. The current usage of PRWs is still low but is increasing. International data show that 1 out of 6 physicians has been rated, and approximately 90% of all ratings on PRWs were positive. Although often a concern, we could not find any evidence of "doctor-bashing". Physicians should not ignore these websites, but rather, monitor the information available and use it for internal and ex-ternal purpose. Several shortcomings limit the significance of the results published on PRWs; some recommendations to address these limitations are presented. CONCLUSIONS Although the number of publications is still low, PRWs are gaining more attention in research. But the current condition of PRWs is lacking. This is the case both in the United States and in Germany. Further research is necessary to increase the quality of the websites, especially from the patients' perspective.

Physician choice making and characteristics associated with using physician-rating websites: cross-sectional study - Emmert, Martin; Meier, Florian; Pisch, Frank; Sander, Uwe (Journal of Medical Internet Research, 2013)
WiSo-Import:2015-03-26:4427